Technical change and employment growth in services: Analytical and policy challenges - Pascal Petit; Luc L. G. Soete (Fondazione Eni Enrico Mattei (FEEM), 1997)
It is generally acknowledged that employment in our economies is increasingly dependent on services. European countries are continuing their gradual move towards a service-based economy with today nearly 70% of the total labour force being employed in service activities. It is also generally acknowledged that services provide the key to future employment growth. However, relatively little attention has been paid to the effects of technical change on services. It is essential to understand whether it will help to develop new markets and welfare or whether it will further the trends of automation. The future of work is at stake in these processes, and the answers are not straightforward. This paper does not attempt to answer all these broad issues. It analyses the dynamics of technical change in services, how it relates with the dynamics of employment and it explores the policies to be pursued at all levels.
Keywords: 330; Technischer Fortschritt; Beschäftigung; Wirtschaftswachstum; Dienstleistungssektor; Theorie